Description of envenomation by the “gusano-pollo” caterpillar (Megalopyge opercularis) in Venezuela. - Luisana Avilán, Luisana Avilán; Belsy Guerrero, Belsy Guerrero; Edinovsky ílvarezEdinovsky ílvarez; Alexis Rodríguez Acosta, Alexis Rodríguez Acosta (Investigación Clínica, 2013)
Â Lepidoptera is a large order of insects, with more than 180,000 species word-wide, showing larval stages of butterflies and moths known as wormlike caterpillars. Almost 12 families of butterflies around the world are capable of causing severe human injuries, varying from dermatitis, renal failure, hemostatic alterations, respiratory failure and neurotoxic symptoms. These caterpillars are coated in long, hair-like setae containing venom to protect themselves against aggressive predators. The setae cause a painful reaction, upon contact, due to presence of neurotoxins. These caterpillars are extensively dispersed all through North America and often, during the dry and wet seasons in tropical regions, being able to sustain two annual larval generations. There exist several species of Megalopyge caterpillars; however, Megalopyge opercularis is the most widely distributed species in Latin America and the United States. This work reports, to our knowledge, the first case of envenomation by the “gusano-pollo” (Megalopyge opercularis), a stinging caterpillar, described in Venezuela. The patient in this report presented severe symptoms, including systemic reactions such as intense hand pain irradiated to the upper arm, restricted swelling, headache, dizziness, serious chest distress and shock-like symptoms that required hospitalization. Symptoms improved upon treatment with opiaceous analgesic drugs.